Positive plate, preparation method thereof and secondary battery
By introducing porphyrin compound grafted silicon particles into the coating layer or functional layer of the positive electrode sheet of the lithium-ion battery, the problem of transition metal ions dissolution in the lithium-ion battery is solved, and the cycle stability and capacity retention rate of the battery are improved. Especially in lithium nickel manganate batteries, the circulation performance has been significantly improved.
Patent Information
- Application Number
- CN202411495005.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-24
AI Technical Summary
During the charging and discharging process of lithium-ion batteries, structural distortion caused by lithium-ion delamination, transition metal ions dissolved into the electrolyte, resulting in a decrease in the battery circulation performance. The additives such as porphyrin added in the prior art will instead lead to long cycles. The battery capacity retention rate decreases and the cycle stability becomes worse.
The grafted silicon particles of porphyrin compound are introduced into the coating layer or functional layer of the positive electrode sheet, and prepared by grafting reaction to form a cladding layer or functional layer of nano-scale particles to efficiently adsorb transition metal ions and reduce lithium ions The migration effect improves battery cycle performance.
The cycle stability and capacity retention rate of the battery are significantly improved, especially in the nickel-manganate lithium battery system, the capacity retention rate of the battery can reach more than 89% after circulating 1000 times at 1C.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery preparation, and in particular to a positive electrode sheet and a preparation method thereof, and a secondary battery. Background Art
[0002] During the charge and discharge process of lithium-ion batteries, the continuous insertion and extraction of lithium ions causes structural distortion, and the transition metal ions in the positive electrode active material will slowly dissolve into the electrolyte, resulting in a decrease in the battery cycle performance.
[0003] The patent application number is CN201510788436.6, and the name is “Positive electrode sheet and secondary battery”. It is disclosed that positive electrode additives such as porphyrin and porphyrin are added to the positive electrode sheet. These positive electrode additives have a great effect on the transition metal ions (Co 2+ 、Ni 2+ , Mn 2+ The results of the performance test show that the capacity retention rate is only about 70% after 500 charge and discharge cycles at a rate of 0.5C. In other words, the cycle performance of the battery has not been effectively improved. Summary of the invention
[0004] To solve the above problems, the purpose of the embodiments of the present application includes providing a positive electrode sheet and a preparation method thereof and a secondary battery, which can improve the adsorption of transition metal ions and enhance the cycle stability of the battery.
[0005] In a first aspect, an embodiment of the present application provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode coating layer disposed on the surface of the positive electrode current collector, wherein the positive electrode coating layer comprises a positive electrode active material and porphyrin compound grafted silicon particles.
[0006] In the above technical scheme, the embodiment of the present application introduces porphyrin compound grafted silicon particles into the positive electrode coating layer. These silicon particles modified by porphyrin grafting have good wettability with the electrolyte and can more efficiently adsorb transition metal ions dissolved from the positive electrode active material during the battery cycle. In addition, the porphyrin compound grafted silicon particles have good durability in the battery system, are not prone to chemical reactions, have little effect on the positive electrode surface interface phase (CEI), and can effectively improve the battery cycle performance while efficiently adsorbing transition metal ions.
[0007] In some embodiments of the present application, a coating layer is provided on the surface of the positive electrode active material, and the coating layer includes porphyrin compound grafted silicon particles.
[0008] Optionally, the coating layer has a thickness of 0.1 nm to 1 μm.
[0009] In the above technical scheme, compared with conventional pure porphyrin additives, porphyrin compound grafted silicon particles form a coating layer on the surface of the positive electrode active material, which can more efficiently improve the cycle performance of the battery. This may be because the porphyrin compound grafted silicon particles are uniformly distributed nano-scale particles with good wettability with the electrolyte. While efficiently adsorbing transition metal ions, they can reduce the impact on the migration of lithium ions between the electrolyte and the positive electrode active material, thereby better improving the cycle performance of the battery.
[0010] In some embodiments of the present application, the positive electrode coating layer includes a positive electrode active layer covering the positive electrode current collector, and a functional layer covering the positive electrode active layer, the positive electrode active layer includes a positive electrode active material, and the functional layer includes porphyrin compound grafted silicon particles.
[0011] Optionally, the thickness of the functional layer is 1 nm to 10 μm.
[0012] In the above technical scheme, compared with conventional pure porphyrin additives, a functional layer including porphyrin compound grafted silicon particles is formed on the surface of the positive electrode active layer, which can more efficiently adsorb transition metal ions and improve the cycle performance of the battery. This may be because the porphyrin compound grafted silicon particles present a uniformly distributed nano-scale particle accumulation in the functional layer and have sufficient pores between the particles, which has little effect on the migration of lithium ions between the diaphragm and the positive electrode sheet, and can reduce the internal resistance of the battery, thereby efficiently adsorbing transition metal ions while better improving the cycle performance of the battery.
[0013] In some embodiments of the present application, the functional layer further includes inorganic oxides and / or polymer glue.
[0014] Optionally, the inorganic oxide includes at least one of boehmite, alumina, silica, titania, ferric oxide or ferrous oxide.
[0015] Optionally, the polymer glue includes at least one of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), polytetrafluoroethylene, polyhexafluoropropylene, polyacrylate, polymethacrylate, polyacrylamide, polymethacrylamide, epoxy resin, polyvinyl pyrrolidone, carboxymethyl cellulose, sodium carboxymethyl cellulose, cellulose or chitosan.
[0016] In the above technical solution, adding inorganic oxides and / or polymers to the functional layer can greatly improve the mechanical strength and processing capability of the functional layer, while reducing the production cost.
[0017] In a second aspect, an embodiment of the present application provides a method for preparing the above-mentioned positive electrode sheet, comprising the following steps:
[0018] A positive electrode current collector is provided, and a positive electrode coating layer is formed on the surface of the positive electrode current collector. The positive electrode coating layer includes positive electrode active materials and porphyrin compound grafted silicon particles.
[0019] In some embodiments of the present application, a method for forming a positive electrode coating layer on a positive electrode current collector includes:
[0020] Coating the surface of the positive electrode active material with porphyrin compound-grafted silicon particles to form a coating layer;
[0021] The positive electrode active material with the coating layer, the binder and the conductive agent are mixed to form an active slurry, and the active slurry is coated on the surface of the positive electrode current collector to form a positive electrode coating layer.
[0022] Optionally, the coating layer is formed by a method including liquid phase coating, ball milling or spraying.
[0023] In some embodiments of the present application, a method for forming a positive electrode coating layer on a positive electrode current collector includes:
[0024] Mixing the positive electrode active material, the binder and the conductive agent to form an active slurry, and coating the active slurry on the surface of the positive electrode current collector to form a positive electrode active layer;
[0025] A functional slurry including porphyrin compound grafted silicon particles is coated on the surface of the positive electrode active layer to form a functional layer. The positive electrode active layer and the functional layer together constitute the positive electrode coating layer.
[0026] Optionally, the functional layer is formed by roller coating or spray coating.
[0027] In some embodiments of the present application, the preparation method of porphyrin compound grafted silicon particles includes:
[0028] The porphyrin compound having an alkenyl group is dissolved in a solvent and mixed with mercapto-functionalized silicon particles, and a grafting reaction is performed under ultraviolet light to prepare the porphyrin compound grafted silicon particles.
[0029] In the above technical scheme, porphyrin compounds with alkenyl groups and mercapto-functionalized silicon particles are selected as raw materials. The alkenyl groups and mercapto groups can directly react under ultraviolet light to complete the grafting. The preparation method is simple, the grafting rate is high, and there are few by-products. The prepared porphyrin compound grafted silicon particles are not easy to undergo chemical reactions in the battery system, the chemical bonds are not easy to break, and have excellent stability.
[0030] In some embodiments of the present application, the mercapto functionalized silicon particles are 3-mercaptopropyl grafted silicon particles. The porphyrin compound having an alkenyl group includes at least one of protoporphyrin, protoporphyrin monomethyl ester, protoporphyrin dimethyl ester, protoporphyrin monosodium salt, protoporphyrin disodium salt, protoporphyrin monolithium salt or protoporphyrin dilithium salt.
[0031] In the above technical solution, specific mercapto-functionalized silicon particles and porphyrin compounds are selected, and the raw materials are simple and easy to obtain, which can improve the reaction efficiency and production cost.
[0032] In some embodiments of the present application, the grafting reaction temperature is 40 to 80° C., and the time is 6 to 24 hours.
[0033] Optionally, the solvent is methanol.
[0034] Optionally, after the grafting reaction, the method further comprises: filtering and washing with methanol, and vacuum drying at 60-100°C.
[0035] In the above technical solution, by controlling the conditions of the grafting reaction, the grafting stability and grafting rate can be enhanced and the purity of the product can be ensured.
[0036] In a third aspect, an embodiment of the present application provides a secondary battery, comprising a negative electrode sheet, a separator, an electrolyte and the above-mentioned positive electrode sheet, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and the electrolyte infiltrates the positive electrode sheet, the negative electrode sheet and the separator.
[0037] Since the positive electrode coating layer is introduced into the positive electrode sheet, the prepared secondary battery has excellent cycle performance, and can especially effectively improve the cycle stability of the nickel manganese oxide lithium battery. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0039] During the charge and discharge process of lithium-ion batteries, the continuous deintercalation of lithium ions causes structural distortion, and the transition metal ions in the positive electrode active material will slowly dissolve into the electrolyte and migrate to the negative electrode surface through the diaphragm, destroying the SEI film on the negative electrode surface, resulting in a decrease in the battery's cycle performance. Although the prior art discloses the addition of metal chelating agents such as porphyrin, porphine and their derivatives to the positive electrode to inhibit the dissolution of transition metal ions, the researchers of this application have found through research that during the long cycle of the battery, compared with the battery system without the addition of metal chelating agents, the presence of these metal chelating agents will instead cause the battery's capacity retention rate to decrease and the battery's cycle stability to deteriorate. In particular, for the nickel manganese oxide lithium battery system, the battery's cycle performance deteriorates significantly.
[0040] Based on this, the researchers of this application have creatively discovered that by grafting functionalized silicon particles with porphyrin compounds to obtain porphyrin compound-grafted silicon particles, adding them to the positive electrode sheet can efficiently adsorb transition metal ions dissolved from the positive electrode active material, and effectively improve the cycle performance of the battery during the long cycle of the battery, especially effectively improve the cycle stability of nickel manganese oxide lithium batteries.
[0041] A positive electrode sheet, a preparation method thereof, and a secondary battery according to an embodiment of the present application are described in detail below.
[0042] The present invention provides a positive electrode sheet and a method for preparing the same, the method comprising the following steps:
[0043] S1: dissolving a porphyrin compound having an alkenyl group in a solvent and mixing the mixture with mercapto-functionalized silicon particles, and performing a grafting reaction under ultraviolet light to prepare porphyrin compound grafted silicon particles.
[0044] The porphyrin compound having an alkenyl group may be protoporphyrin, protoporphyrin monomethyl ester, protoporphyrin dimethyl ester, protoporphyrin monosodium salt, protoporphyrin disodium salt, protoporphyrin monolithium salt, protoporphyrin dilithium salt. The mercapto functionalized silicon particles may be 3-mercaptopropyl grafted silicon particles.
[0045] It should be noted that the examples of the present application only list several porphyrin compounds having alkenyl groups, but are not limited thereto. Other porphyrins or porphyrin derivatives having alkenyl groups may be used in practical applications.
[0046] The thiol loading of the thiol-functionalized silicon particles may be 0.1 mmol / g to 10 mmol / g. As an example, the thiol loading of the thiol-functionalized silicon particles may be 0.3 mmol / g. By correspondingly controlling the thiol loading, the thiol in the thiol-functionalized silicon particles can fully react with the olefinic group in the porphyrin compound.
[0047] In the grafting reaction, the molar ratio of the alkenyl group in the porphyrin compound having an alkenyl group and the mercapto group in the mercapto-functionalized silicon particles can be controlled to be about (1-5): 1. By controlling the excess of mercapto groups, the grafting rate after the reaction can reach 100%.
[0048] The conditions of the grafting reaction include: the grafting reaction temperature is 40 to 80°C, and the time is 6 to 24 hours. The solvent can be methanol, preferably anhydrous methanol. After the grafting reaction, the following steps are further performed: filtering and washing with methanol, and vacuum drying at 60 to 100°C. By controlling the grafting reaction conditions, the efficiency of the grafting reaction can be improved and the purity of the product can be ensured.
[0049] As an example, the general structural formula of porphyrin compound grafted silicon particles is shown in formula (I):
[0050]
[0051] Among them, R3, R5, R7, R8, R 10 , R 12 , R 13 , R 15 , R 17 , R 18 , R 20 are each independently phenyl, vinyl, allyl, C n H 2n+1 , C n H 2n OH, C n H 2n CHO, C n H 2n COOH, C n H 2n COONa、C n H 2n COOLi, C n H 2n COOC n H 2n , C n H 2n SH, n is an integer between 0 and 20; i and j are each independently an integer between 0 and 10.
[0052] As a specific example, the grafting reaction process of protoporphyrin IX and 3-mercaptopropyl grafted silicon particles is shown in the following formula:
[0053]
[0054] S2: providing a positive electrode current collector, and forming a positive electrode coating layer on the surface of the positive electrode current collector, wherein the positive electrode coating layer comprises a positive electrode active material and porphyrin compound grafted silicon particles.
[0055] Among them, the positive electrode current collector can be aluminum foil or carbon-coated aluminum foil. The positive electrode active material can be LiMPO4 or LiNO2, wherein M can be at least one of Fe, Co, Ni or Mn, and N can be at least one of Ni, Co, Mn or Al. As an example, the positive electrode active material can be lithium iron phosphate (referred to as LFP), lithium manganese iron phosphate (referred to as LMFP), lithium manganese oxide (referred to as LMO), lithium cobalt oxide (referred to as LCO), lithium nickel manganese oxide (referred to as LNMO), lithium nickel cobalt manganese oxide (referred to as NCM), and lithium nickel cobalt aluminum oxide (referred to as NCA). The particle size of the positive electrode active material can be 10nm to 100μm.
[0056] As an example, a method for forming a positive electrode coating layer on the surface of a positive electrode current collector may include:
[0057] Coating the surface of the positive electrode active material with porphyrin compound-grafted silicon particles to form a coating layer;
[0058] Mixing the positive electrode active material with the coating layer, a binder and a conductive agent to form an active slurry, and coating the active slurry on the surface of the positive electrode current collector to form a positive electrode coating layer;
[0059] The coating layer can be provided on the surface of the positive electrode active material by liquid phase coating, fluidized bed spraying, and high-speed ball milling. As a specific example, a suspension of porphyrin compound grafted silicon particles can be sprayed on the surface of the positive electrode active material on a fluidized bed and then dried to obtain the coating layer.
[0060] The thickness of the coating layer can be 0.1 nm to 1 μm, for example but not limited to any one of 0.1 nm, 0.01 μm, 1 μm or any range between the two. By controlling the thickness of the coating layer, the effect of adsorbing transition metal ions can be ensured, while reducing the influence on ion migration, and ensuring the cycle stability of the battery during the long cycle of the battery.
[0061] As another example, a method for forming a positive electrode coating layer on a surface of a positive electrode current collector may include:
[0062] Mixing the positive electrode active material, the binder and the conductive agent to form an active slurry, and coating the active slurry on the surface of the positive electrode current collector to form a positive electrode active layer;
[0063] A functional slurry including porphyrin compound grafted silicon particles is coated on the surface of the positive electrode active layer to form a functional layer. The positive electrode active layer and the functional layer together constitute the positive electrode coating layer.
[0064] When forming a functional layer on the surface of the positive electrode active layer, the raw materials of the functional layer may also include inorganic oxides and / or polymer glues. Among them, the inorganic oxides may be selected from at least one of boehmite, alumina, silicon dioxide, titanium dioxide, ferric oxide or ferric oxide. The polymer glue may be selected from polyvinylidene fluoride, poly(vinylidene fluoride), At least one of polytetrafluoroethylene, polyhexafluoropropylene, polyacrylate, polymethacrylate, polyacrylamide, polymethacrylamide, epoxy resin, polyvinyl pyrrolidone, carboxymethyl cellulose, sodium carboxymethyl cellulose, cellulose or chitosan. The weight average molecular weight of the polymer may be 1,000 to 3,000,000.
[0065] The mass ratio of the porphyrin compound grafted silicon particles, the inorganic oxide and the polymer glue can be (1-99):(0-99):(0-99).
[0066] As an example, the thickness of the functional layer may be 1 nm to 10 μm, for example but not limited to, any one of 1 nm, 1 μm, and 10 μm, or a range between any two of the thicknesses.
[0067] The functional layer can be formed on the surface of the positive electrode active layer by roller coating, spray coating, etc. As an example, the porphyrin compound grafted silicon particles and polymer can be mixed to form a slurry, and then the slurry is ultrasonically sprayed on the surface of the positive electrode active layer and dried to form the functional layer.
[0068] It should be noted that the binder and the conductive agent are both conventionally selected in the art. For example, the binder may be polyvinylidene fluoride, and the conductive agent may be conductive carbon or the like.
[0069] In addition, an embodiment of the present application provides a secondary battery, including a negative electrode sheet, a separator, an electrolyte and the above-mentioned positive electrode sheet, the separator is located between the positive electrode sheet and the negative electrode sheet, and the electrolyte infiltrates the positive electrode sheet, the negative electrode sheet and the separator.
[0070] It should be noted that the negative electrode sheet, separator and electrolyte can all be conventionally selected in the art, and are not limited in this application, and can be selected according to actual application needs.
[0071] It should be noted that the embodiments of the present application only list some positive electrode active materials used in lithium-ion batteries, but the type of battery is not limited. In actual application, sodium-ion batteries and the like can also be used.
[0072] The features and performance of the present application are further described in detail below in conjunction with embodiments and comparative examples.
[0073] Example 1-1
[0074] The present application embodiment provides a battery PC1, comprising the following steps:
[0075] (1) Preparation of 3-mercaptopropyl grafted silicon particles
[0076] Take 100g silicon particles (particle diameter is 100nm) and slowly add them to 1L of Piranha solution under magnetic stirring, then stir at 90℃ for 1h, filter and wash with a large amount of pure water after completion, and vacuum dry at 60℃. Take the above activated silicon particles, then add 600mL of toluene solution of 3-mercaptopropyltrimethoxysilane with a concentration of 60mmol / L, and stir the reaction for 12h. Finally, filter and wash the above silicon particles with acetone and pure water, vacuum dry at 120℃ for use, and obtain 3-mercaptopropyl grafted silicon particles. Among them, the thiol loading is 0.3mmol / g.
[0077] (2) Preparation of positive electrode active materials
[0078] Take 134.9g of protoporphyrin IX (Aladdin, CAS: 553-12-8) and dissolve it in 1214.1g of anhydrous methanol, then add 100g of 3-mercaptopropyl grafted silicon particles prepared in step (1), stir and disperse at 60°C and irradiate with ultraviolet light for 12h to obtain a suspension containing protoporphyrin grafted silicon particles.
[0079] The suspension containing protoporphyrin-grafted silicon particles was sprayed on the surface of lithium nickel manganese oxide (particle diameter 6 μm) on a fluidized bed, and then dried at 80°C, washed with 12,000 g of anhydrous methanol, and then vacuum dried at 80°C for standby use to obtain a positive electrode active material with a coating layer on the surface. The thickness of the coating layer was 0.3 μm.
[0080] (3) Preparation of positive electrode
[0081] Take 96g of the above positive electrode active material, 1.8g of polyvinylidene fluoride, and 2.2g of conductive carbon, disperse them at high speed for 8h to obtain active slurry, then coat the active slurry on both sides of an aluminum foil with a thickness of 12μm, then dry it at 100℃, and cut it into positive electrode sheets for use.
[0082] (4) Preparation of negative electrode
[0083] Take 95.6g of artificial graphite, 1.5g of carboxymethyl cellulose, 1.1g of conductive carbon, and 4.5g of styrene-butadiene rubber latex (solid content 40wt%), disperse them at high speed for 8h, then coat them on both sides of a copper foil with a thickness of 8μm, then dry them at 100℃, and cut them into negative electrode sheets for use.
[0084] (5) Preparation of batteries
[0085] The positive electrode sheet, negative electrode sheet and polyethylene separator with a thickness of 14 μm are taken to form a small soft-pack battery through a lamination process, and then the battery PC1 is obtained by normal liquid injection, formation and capacity separation.
[0086] Example 1-2
[0087] The present embodiment provides a battery PC2, which differs from the embodiment 1-1 only in that:
[0088] (2) Preparation of positive electrode active materials
[0089] 134.9 g of protoporphyrin IX (Aladdin, CAS: 553-12-8) was dissolved in 1214.1 g of anhydrous methanol, and then 100 g of 3-mercaptopropyl grafted silicon particles were added, stirred and dispersed at 60°C, and irradiated with ultraviolet light for 12 hours. Afterwards, the mixture was filtered and washed with 12000 g of anhydrous methanol, and then vacuum dried at 80°C to obtain protoporphyrin grafted silicon particles.
[0090] The protoporphyrin-grafted silicon particles and lithium nickel manganese oxide (particle diameter of 6 μm) were milled at high speed for 24 hours in a high-energy ball mill to obtain a positive electrode active material with a coating layer on the surface, wherein the thickness of the coating layer was 0.5 μm.
[0091] Examples 1-3
[0092] The present application embodiment provides a battery PC3, which differs from the embodiment 1-1 only in that: in step (2), the nickel manganese oxide is replaced with nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2). The thickness of the coating layer is 0.3 μm.
[0093] Examples 1-4
[0094] The present application embodiment provides a battery PC4, which differs from the embodiment 1-2 only in that: in step (2), the nickel manganese oxide is replaced with nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2). The thickness of the coating layer is 0.5 μm.
[0095] Examples 1-5
[0096] The present embodiment provides a battery PC5, which differs from the embodiment 1-1 only in that the lithium nickel manganese oxide is replaced with lithium iron phosphate (LFP, chemical formula LiFePO4) in step (2). The thickness of the coating layer is 0.2 μm.
[0097] Examples 1-6
[0098] The present embodiment provides a battery PC6, which differs from the embodiment 1-2 only in that the lithium nickel manganese oxide is replaced with lithium iron phosphate (LFP for short, chemical formula LiFePO4) in step (2). The thickness of the coating layer is 0.3 μm.
[0099] Comparative Example 1-1
[0100] The comparative example of the present application provides a battery RC1, which is different from Example 1-1 only in that: in step (2), the positive electrode active material is lithium nickel manganese oxide without any treatment, that is, no coating layer is provided on the surface.
[0101] Comparative Example 1-2
[0102] The comparative example of the present application provides a battery RC2, which differs from Examples 1-3 only in that: in step (2), the positive electrode active material is lithium nickel cobalt manganese oxide without any treatment, that is, no coating layer is provided on the surface.
[0103] Comparative Examples 1-3
[0104] The comparative example of the present application provides a battery RC3, which differs from Examples 1-5 only in that: in step (2), the positive electrode active material is lithium iron phosphate without any treatment, that is, no coating layer is provided on the surface.
[0105] Comparative Examples 1-4
[0106] The comparative example of the present application provides a battery RC4, which differs from Example 1-1 only in that in step (2), protoporphyrin IX is used instead of protoporphyrin-grafted silicon particles to form the coating layer. Step (2) specifically includes the following steps:
[0107] (2) Preparation of positive electrode active materials
[0108] 134.9 g of protoporphyrin IX was dissolved in 1214.1 g of anhydrous methanol, sprayed on the surface of lithium nickel manganese oxide on a fluidized bed, and then vacuum dried at 80° C. for later use to obtain a positive electrode active material with a protoporphyrin coating layer on the surface, wherein the coating layer has a thickness of 2 μm.
[0109] Some key preparation conditions of the positive electrode sheets in the above examples and comparative examples are shown in Table 1.
[0110] Table 1 Partial preparation conditions of positive electrode sheets in Examples and Comparative Examples
[0111] Battery ID Positive electrode active material Cladding Preparation method PC1 Lithium Nickel Manganese Oxide Protoporphyrin IX grafted silica particles Fluidized bed spray PC2 Lithium Nickel Manganese Oxide Protoporphyrin IX grafted silica particles High speed ball mill PC3 Lithium Nickel Cobalt Manganese Oxide Protoporphyrin IX grafted silica particles Fluidized bed spray PC4 Lithium Nickel Cobalt Manganese Oxide Protoporphyrin IX grafted silica particles High speed ball mill PC5 Lithium Iron Phosphate Protoporphyrin IX grafted silica particles Fluidized bed spray PC6 Lithium Iron Phosphate Protoporphyrin IX grafted silica particles High speed ball mill RC1 Lithium Nickel Manganese Oxide / / RC2 Lithium Nickel Cobalt Manganese Oxide / / RC3 Lithium Iron Phosphate / / RC4 Lithium Nickel Manganese Oxide Protoporphyrin IX Fluidized bed spray
[0112] Test Example 1
[0113] The batteries prepared in the above examples and comparative examples were cycled 1000 times at room temperature and 1C to test the cycle performance, and the content of transition metal ions in the electrolyte after 1000 cycles was measured. The specific test method is as follows:
[0114] 1. Cycle performance test
[0115] The battery of the embodiment and the battery of the comparative example were subjected to cycle performance test according to the following steps:
[0116] (1) Leave for 1 minute;
[0117] (2) Discharge from the open circuit voltage to the lower limit voltage with a constant current of 1C;
[0118] (3) Leave for 1 min;
[0119] (4) Charge at a constant current of 1C to the upper voltage limit, and then charge at a constant voltage of 0.05C;
[0120] (5) Leave for 1 min;
[0121] (6) Discharge at a constant current of 1C to the lower limit voltage;
[0122] (7) Leave for 1 min;
[0123] (8) Repeat steps (4) to (7) for 1000 times.
[0124] Among them, the voltage upper limit of Examples 1-1 to 1-2, Comparative Examples 1-1 and Comparative Examples 1-4 is 4.8V, and the voltage lower limit is 3.5V; the voltage upper limit of Examples 1-3 to 1-4 and Comparative Examples 1-2 is 4.3V, and the voltage lower limit is 2.8V; the voltage upper limit of Examples 1-5 to 1-6 and Comparative Examples 1-3 is 3.85V, and the voltage lower limit is 2.5V. The cycle performance test results are shown in Table 2.
[0125] 2. Transition metal ion content test
[0126] The small soft-pack battery after 1000 cycles at room temperature was disassembled, and 0.5 g of free electrolyte was extracted, and then diluted to 10 g with dimethyl carbonate. The diluted sample was taken and the contents of Fe, Co, Ni, and Mn in the sample were determined by ICP external standard method. The measurement results are shown in Table 3.
[0127] Table 2 Summary of cycle performance of embodiments and comparative examples
[0128]
[0129]
[0130] Table 3 Summary of the content of transition metal ions in the embodiments and comparative examples
[0131]
[0132] From the test results of Table 2 and Table 3, it can be seen that after the batteries of Examples 1-1 to 1-6 are cycled 1000 times at room temperature at 1C, the content of transition metal ions in the electrolyte is relatively low, and the minimum can reach 8ppm. Correspondingly, the batteries of Examples 1-1 to 1-6 have excellent cycle performance, and after 1000 cycles at room temperature at 1C, the capacity retention rate is not less than 89%, and the maximum can reach 95%.
[0133] By comparing the performance test results of Example 1-1 and Comparative Example 1-1, Example 1-3 and Comparative Example 1-2, and Example 1-3 and Comparative Example 1-3, it can be seen that in the present application, by setting a porphyrin compound grafted silicon particle coating layer on the surface of the positive electrode active material, transition metal ions can be efficiently adsorbed, and the cycle performance of the battery can be improved. By comparing the performance test results of Example 1-1 and Comparative Example 1-4, it can be seen that although the pure porphyrin coating layer can also adsorb a certain amount of transition metal ions, it has poor stability and poor adsorption effect during long-term circulation, and electrochemical oxidation will occur slowly. After 1000 cycles, the capacity retention rate drops to 32%, and the cycle performance is significantly worse than that of Example 1-1.
[0134] The above-mentioned embodiment 1-1 and comparative example 1-1 and comparative example 1-4 are batteries of nickel manganese oxide lithium system, the above-mentioned embodiment 1-3 and comparative example 1-2 are batteries of nickel cobalt manganese oxide lithium system, and the above-mentioned embodiment 1-5 and comparative example 1-3 are batteries of lithium iron phosphate system. It can be seen from the contents of Table 2 and Table 3 that for batteries of different positive electrode active material systems, the technical solution provided by the present application can efficiently adsorb transition metal ions dissolved from the positive electrode active material during the cycle process by forming a coating layer including porphyrin compound grafted silicon particles on the surface of the positive electrode active material, and effectively improve the cycle performance during the long cycle process. In particular, it can effectively improve the cycle stability of the nickel manganese oxide lithium battery system.
[0135] Example 2-1
[0136] The present application embodiment provides a battery PB1, comprising the following steps:
[0137] (1) Preparation of protoporphyrin-grafted silica particles
[0138] Take 100g silicon particles (particle diameter is 100nm) and slowly add them to 1L of Piranha solution under magnetic stirring, then stir at 90℃ for 1h, filter and wash with a large amount of pure water and vacuum dry at 60℃. Then take the above activated silicon particles, add 600mL of toluene solution of 3-mercaptopropyltrimethoxysilane with a concentration of 60mmol / L, and stir the reaction for 12h. Finally, filter and wash the above silicon particles with acetone and pure water, vacuum dry at 120℃ for use, and obtain 3-mercaptopropyl grafted silicon particles. Among them, the thiol loading is 0.3mmol / g.
[0139] 134.9 g of protoporphyrin IX (Aladdin, CAS: 553-12-8) was dissolved in 1214.1 g of anhydrous methanol, and then 100 g of 3-mercaptopropyl grafted silicon particles were added. The mixture was stirred at 60 ° C and irradiated with ultraviolet light for 12 h. After that, it was filtered and washed with 12000 g of anhydrous methanol, and then vacuum dried at 80 ° C to obtain protoporphyrin IX grafted silicon particles.
[0140] (2) Preparation of positive electrode
[0141] Take 96g of lithium nickel manganese oxide, 1.8g of polyvinylidene fluoride, and 2.2g of conductive carbon, and obtain an active slurry after high-speed dispersion for 8 hours. The active slurry is coated on both sides of an aluminum foil with a thickness of 12μm, and then dried at 100°C to form positive electrode active layers on both sides of the aluminum foil.
[0142] Take 10g of polyvinylidene fluoride (weight average molecular weight of 600,000) and dissolve it in 500g of NMP; then add 90g of protoporphyrin grafted silicon particles in step (1) and disperse at high speed for 5h to obtain functional slurry. Then ultrasonically spray the functional slurry on the surface of the positive electrode active layer to form a functional layer with a thickness of 1μm, and then cut it into positive electrode sheets and dry it at 100℃ for use.
[0143] (3) Preparation of negative electrode sheet
[0144] Take 95.6g of artificial graphite, 1.5g of carboxymethyl cellulose, 1.1g of conductive carbon, and 4.5g of styrene-butadiene rubber latex (solid content is 40wt%), disperse them at high speed for 8h, then coat them on both sides of a copper foil with a thickness of 8μm, then dry them at 100℃, and cut them into negative electrode sheets for use.
[0145] (4) Preparation of batteries
[0146] The above-mentioned positive electrode sheet, negative electrode sheet and polyethylene separator with a thickness of 14 μm were used to form a small soft-pack battery through a lamination process, and then the battery PB1 was obtained by normal liquid injection, formation and capacity separation.
[0147] Example 2-2
[0148] The present embodiment provides a battery PB2, which differs from the embodiment 2-1 only in that:
[0149] (2) Preparation of positive electrode
[0150] Take 96g of lithium nickel manganese oxide, 1.8g of polyvinylidene fluoride, and 2.2g of conductive carbon, disperse them at high speed for 8h to obtain an active slurry, coat the active slurry on both sides of an aluminum foil with a thickness of 12μm, and then dry it at 100°C to form positive electrode active layers on both sides of the aluminum foil.
[0151] Take 10g of polyvinylidene fluoride (weight average molecular weight 600,000), dissolve it in 600g of NMP, then add 10g of silicon dioxide and 80g of protoporphyrin grafted silicon particles and disperse at high speed for 5h to obtain functional slurry. Then ultrasonically spray the functional slurry on the surface of the above positive electrode active layer to form a functional layer with a thickness of 1μm, and then cut it into positive electrode sheets and dry it at 100℃ for use.
[0152] Example 2-3
[0153] The present embodiment provides a battery PB3, which differs from the embodiment 2-1 only in that: in step (2), the lithium nickel manganese oxide is replaced with lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2).
[0154] Embodiment 2-4
[0155] The present embodiment provides a battery PB4, which differs from the embodiment 2-2 only in that: in step (2), the nickel manganese oxide is replaced with nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2).
[0156] Embodiment 2-5
[0157] The embodiment of the present application provides a battery PB5, which differs from the embodiment 2-1 only in that in step (2), the lithium nickel manganese oxide is replaced by lithium iron phosphate (LFP for short, chemical formula LiFePO4).
[0158] Embodiment 2-6
[0159] The embodiment of the present application provides a battery PB6, which differs from the embodiment 2-2 only in that in step (2), the lithium nickel manganese oxide is replaced by lithium iron phosphate (LFP for short, chemical formula LiFePO4).
[0160] Comparative Example 2-1
[0161] The comparative example of the present application provides a battery RB1, which is different from Example 2-1 only in that a functional layer is not formed on the surface of the positive electrode active layer in step (2).
[0162] Comparative Example 2-2
[0163] The comparative example of the present application provides a battery RB2, which is different from Examples 2-3 only in that a functional layer is not formed on the surface of the positive electrode active layer in step (2).
[0164] Comparative Examples 2-3
[0165] The comparative example of the present application provides a battery RB3, which is different from embodiments 2-5 only in that a functional layer is not formed on the surface of the positive electrode active layer in step (2).
[0166] Comparative Examples 2-4
[0167] The comparative example of the present application provides a battery RB4, which differs from Example 2-1 only in that: in step (2), protoporphyrin is used instead of protoporphyrin-grafted silicon particles to form a functional layer. Step (2) specifically includes:
[0168] Take 96g of lithium nickel manganese oxide, 1.8g of polyvinylidene fluoride, and 2.2g of conductive carbon, disperse them at high speed for 8h to form an active slurry, coat the active slurry on both sides of an aluminum foil with a thickness of 12μm, and then dry it at 100℃ to form positive electrode active layers on both sides of the aluminum foil.
[0169] Take 10g of polyvinylidene fluoride (weight average molecular weight of 600,000) and dissolve it in 500g of NMP. Then add 90g of protoporphyrin IX and disperse it at high speed for 5h to obtain functional slurry. Then ultrasonically spray the functional slurry on the surface of the positive electrode active layer to form a functional layer with a thickness of 1μm, and then cut it into positive electrode sheets and dry it at 100℃ for use.
[0170] Some key preparation conditions of the positive electrode sheets in the above embodiments and comparative examples are shown in Table 4.
[0171] Table 4 Partial preparation conditions of positive electrode sheets in Examples and Comparative Examples
[0172]
[0173] Test Example 2
[0174] The batteries prepared in the above examples and comparative examples were cycled 1000 times at room temperature and 1C to test the cycle performance, and the content of transition metal ions in the electrolyte after 1000 cycles was measured. The specific test method is the same as that of Experimental Example 1. The performance test results are shown in Tables 5 and 6.
[0175] Table 5 Summary of cycle performance of embodiments and comparative examples
[0176]
[0177]
[0178] Table 6 Summary of transition metal ion contents in the embodiments and comparative examples
[0179]
[0180] From the performance test results of Table 5 and Table 6, it can be seen that after the batteries of Examples 2-1 to 2-6 are cycled 1000 times at room temperature at 1C, the content of transition metal ions in the electrolyte is relatively low, and the minimum can reach 5ppm. Correspondingly, the batteries of Examples 2-1 to 2-6 have excellent cycle performance, and after 1000 cycles at room temperature at 1C, the capacity retention rate is not less than 90%, and the maximum can reach 96%.
[0181] By comparing the performance test results of Example 2-1 and Comparative Example 2-1, Example 2-3 and Comparative Example 2-2, and Example 2-5 and Comparative Example 2-3, it can be seen that in the present application, by setting a functional layer including porphyrin compound grafted silicon particles on the surface of the positive electrode active layer, transition metal ions can be efficiently adsorbed and the cycle performance of the battery can be improved. By comparing the performance test results of Example 2-1 and Comparative Example 2-4, it can be seen that although the pure porphyrin functional layer can also adsorb a certain amount of transition metal ions, it has poor stability and poor adsorption effect during long-term cycles, and electrochemical oxidation will occur slowly. After 1000 cycles at room temperature 1C, the capacity retention rate is reduced to 13%, and the cycle performance is significantly worse than that of Example 2-1.
[0182] The above-mentioned Example 2-1 and Comparative Example 2-1 and Comparative Example 2-4 are batteries of a nickel manganese oxide lithium system, the above-mentioned Example 2-3 and Comparative Example 2-2 are batteries of a nickel cobalt manganese oxide lithium system, and the above-mentioned Example 2-5 and Comparative Example 2-3 are batteries of a lithium iron phosphate system. It can be seen from the contents of Table 5 and Table 6 that for batteries of different positive electrode active material systems, the technical solution provided by the present application can efficiently adsorb transition metal ions dissolved from the positive electrode active material during the cycle by forming a functional layer including porphyrin compound grafted silicon particles on the surface of the positive electrode active layer, and effectively improve the cycle performance during the long cycle process. In particular, it can effectively improve the cycle stability of the nickel manganese oxide lithium battery system.
[0183] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode coating layer arranged on the surface of the positive electrode current collector, wherein the positive electrode coating layer comprises positive electrode active materials and porphyrin compound grafted silicon particles.
2. The positive electrode sheet according to claim 1, characterized in that: The surface of the positive electrode active material is provided with a coating layer, and the coating layer includes porphyrin compound grafted silicon particles; Optionally, the coating layer has a thickness of 0.1 nm to 1 μm.
3. The positive electrode sheet according to claim 1, characterized in that: The positive electrode coating layer comprises a positive electrode active layer covering the positive electrode current collector, and a functional layer covering the positive electrode active layer, wherein the positive electrode active layer comprises the positive electrode active material, and the functional layer comprises the porphyrin compound grafted silicon particles; Optionally, the thickness of the functional layer is 1 nm to 10 μm.
4. The positive electrode sheet according to claim 3, characterized in that: The functional layer further comprises inorganic oxides and / or polymer glue; Optionally, the inorganic oxide includes at least one of boehmite, alumina, silica, titanium dioxide, ferric oxide or ferrosoferric oxide; Optionally, the polymer glue includes at least one of polyvinylidene fluoride, poly(vinylidene fluoride hexafluoropropylene), polytetrafluoroethylene, polyhexafluoropropylene, polyacrylate, polymethacrylate, polyacrylamide, polymethacrylamide, epoxy resin, polyvinyl pyrrolidone, carboxymethyl cellulose, sodium carboxymethyl cellulose, cellulose or chitosan.
5. A method for preparing a positive electrode sheet according to any one of claims 1 to 4, characterized in that: The following steps are involved: A positive electrode current collector is provided, and the positive electrode coating layer is formed on the surface of the positive electrode current collector. The positive electrode coating layer includes the positive electrode active material and the porphyrin compound grafted silicon particles.
6. The preparation method according to claim 5, characterized in that: The method for forming the positive electrode coating layer on the positive electrode current collector comprises: Coating the porphyrin compound-grafted silicon particles on the surface of the positive electrode active material to form a coating layer; Mixing the positive electrode active material with the coating layer, a binder and a conductive agent to form an active slurry, and coating the active slurry on the surface of the positive electrode current collector to form the positive electrode coating layer; Optionally, the coating layer is formed by a method comprising liquid phase coating, ball milling or spraying.
7. The preparation method according to claim 5, characterized in that: The method for forming the positive electrode coating layer on the positive electrode current collector comprises: Mixing the positive electrode active material, the binder and the conductive agent to form an active slurry, and coating the active slurry on the surface of the positive electrode current collector to form a positive electrode active layer; A functional slurry including porphyrin compound grafted silicon particles is coated on the surface of the positive electrode active layer to form a functional layer, wherein the positive electrode active layer and the functional layer together constitute the positive electrode coating layer; Optionally, the method for forming the functional layer includes roller coating or spray coating.
8. The preparation method according to claim 5, characterized in that: The preparation method of the porphyrin compound grafted silicon particles comprises the following steps: The porphyrin compound having an alkenyl group is dissolved in a solvent and mixed with mercapto-functionalized silicon particles, and a grafting reaction is performed under ultraviolet light to prepare the porphyrin compound grafted silicon particles.
9. The preparation method according to claim 8, characterized in that: The mercapto-functionalized silicon particles are 3-mercaptopropyl grafted silicon particles; The porphyrin compound having an alkenyl group includes at least one of protoporphyrin, protoporphyrin monomethyl ester, protoporphyrin dimethyl ester, protoporphyrin monosodium salt, protoporphyrin disodium salt, protoporphyrin monolithium salt or protoporphyrin dilithium salt; Optionally, the grafting reaction is carried out at a temperature of 40 to 80° C. and for a time of 6 to 24 hours.
10. A secondary battery, characterized in that: The invention comprises a negative electrode sheet, a separator, an electrolyte and the positive electrode sheet as claimed in any one of claims 1 to 4, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and the electrolyte infiltrates the positive electrode sheet, the negative electrode sheet and the separator.
Citation Information
Patent Citations
Secondary battery
JP1994168739A
Cathode material for nonaqueous electrolyte secondary battery, electrode structure manufactured using cathode material, and nonaqueous electrolyte secondary battery
JP2004200010A
Synthesis of homogeneously silica-coated magnetic microparticles and its Application to Heterogeneous Catalyst for Olefin Oxidation
KR101990215B1
Lithium ion-based internal hybrid electrochemical energy storage cell
US20190108948A1
